Technical Debt Guild: When experience and engagement improve Technical Debt Management - Detofeno, Thober; Reinehr, Sheila; Malucelli, Andreia (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2021)
Efficient Technical Debt Management (TDM) requires specialized guidance so that decisions taken are oriented to add value to the business. Because it is a complex problem that involves several variables, TDM requires a systemic look that considers professionals’ experiences from different specialties. Guilds have been a means technology companies using the Spotify methodology have found to unite specialized professionals around a common interest. This paper presents the experience in implementing a guild to support TDM’s source code activities in a software development organization, using the action research method. The project lasted two years, and approximately 100 developers were involved in updating about 63,300 source-code files. The actions resulting from the TDM guild’s efforts impacted the company’s culture by introducing new development practices and standards. Besides, they positively influenced the quality of the artifact delivered by the developers. This study shows that, as the company acquires maturity in TDM, it increases the need for professionals dedicated to TDM’s activities.